Pedagogia da sororidade : uma etnografia com mulheres lideranças de Ribeirão das Neves - MG - Simone de Oliveira Mestre (2023)
Empirically, an abyss can be seen between the political participation of women in the governmental sphere and in civil society. If, on one hand, their presence is predominant in the leadership of movements, articulations and community actions; on the other hand, there is a low representation in the Legislative, Executive and Judiciary branches of government. In this context, how can one investigate the participation of women in social mobilizations? How do stigmas, male chauvinism, and exclusion affect the lives of community leaders? Facing these questions, it is important to emphasize that it is not the purpose of this PhD research to provide an explanatory framework about all the gender disparities existing in the Brazilian political context, especially in the governmental sphere, but rather to understand which motivations lead women to engage in a collective fight, especially in contexts marked by social inequalities. In this way, we start from the experience of women living in Ribeirão das Neves, a city seen as marginalized by residents of the state capital, the metropolitan region of Belo Horizonte and other adjacent cities, due to the stigmas of "dorm city", "violent city" and "city of prisons". The goal is to understand how these women perceive and construct themselves as community leaders in a territory located in a stigmatized locus. The aim is to identify the impacts of the territory's stigmatization process on these women, to verify how the social markers of difference are articulated in their practices and experiences, and to understand how caring relationships and agencies integrate and shape sociability practices. To this end, we used a qualitative methodological approach, by conducting ethnographic research, prioritizing the biographical approach of women leaders who live and work in the city, produced through in-depth interviews, participant observation in rounds of conversations in loco, WhatsApp groups and social networks such as Instagram and Facebook, circulation through the territory and participation in events and meetings. The analyses and reflections of the data obtained during the fieldwork indicate that the community leaders incorporate, institute, implement and promote what I call "pedagogy of sorority". The results show that these women, as entrepreneurs, mobilize both the stigma of the territory and the debates about gender inequalities as discursive elements in the process of mobilizing networks and formative practices in the city, reinforcing the theoretical perspectives that consider social movements as non-formal educational spaces. Moreover, it could be noticed that being a leader is a social marker that articulates with other social markers of difference that, simultaneously, highlight aspects of vulnerability of these women and symbolize an acquisition of symbolic, cultural, and political capitals. Therefore, the pedagogy of sorority is pointed out, in this thesis, as a set of tactics, formations, access devices and processes that are absorbed and shared by women throughout their trajectory of engagement in the struggle for reparatory, emancipatory and regulatory public policies.